La memoria de responsabilidad social empresarial - Echaiz Moreno, Daniel (Revista de Derecho, 2019)
The company develops contemporary converge in a world where corporate governance and corporate social responsibility as two pillars that guide its action. Thus, the Corporate Social Responsibility Report shows how the company is committed to sustainable development of their social environment. It is not sufficient for the preparation and submission of the report required by the Corporations Act, but now the market advocates also have it. In this paper we present the most important aspects of this new figure that is gaining ground abroad and deserves to be treated in our country.